VISCOELASTIC AND EQUILIBRIUM SHEAR PROPERTIES OF HUMAN MENISCUS: RELATIONSHIPS WITH TISSUE STRUCTURE AND COMPOSITION - Norberg, Christopher (J Biomech, 2021)
The meniscus is crucial in maintaining the knee function and protecting the joint from secondary pathologies, including osteoarthritis. Although most of the mechanical properties of human menisci have been characterized, to our knowledge, its dynamic shear properties have never been reported. Moreover, little is known about meniscal shear properties in relation to tissue structure and composition. This is crucial to understand mechanisms of meniscal injury, as well as, in regenerative medicine, for the design and development of tissue engineered scaffolds mimicking the native tissue. Hence, the objective of this study was to characterize the dynamic and equilibrium shear properties of human meniscus in relation to its anisotropy and composition. Specimens were prepared from the axial and the circumferential anatomical planes of medial and lateral menisci. Frequency sweeps and stress relaxation tests yielded storage (G’) and loss moduli (G’’), and equilibrium shear modulus (G). Correlations of moduli with water, glycosaminoglycans (GAGs), and collagen content were investigated. The meniscus exhibited viscoelastic behavior. Dynamic shear properties were related to tissue composition: negative correlations were found between G’, G’’ and G, and meniscal water content; positive correlations were found for G’ and G’’ with GAG and collagen (only in circumferential samples). Circumferential samples, with collagen fibers orthogonal to the shear plane, exhibited superior dynamic mechanical properties, with G’ ~70 kPa and G’’ ~10kPa, compared to those of the axial plane ~15 kPa and ~1kPa, respectively. Fiber orientation did not affect the values of G, which ranged from ~50 to ~100kPa.